Study of the adhesion on overmoulded parts with thermoplastic/LSR combination - Barros, G. (2011)
Multi-material parts with PBT/LSR combination were produced in two separate steps, one for the injection of PBT parts, and a second for the LSR overmoulding. The aim of this work is to study the influence of process-parameters such as mold temperature, curing time, temperature of the PBT insert before performing the overmoulding with LSR, on the adhesion with LSR’s. The effect on the adhesion of the amount of glass fiber content on the PBT was also studied. The adhesion between the materials was measured using a peel-test 90º. The results of the peel-test indicated that the adhesion is influenced by the parameters described. The adhesion between the two materials increase significantly with the increase of the processparameters.